Study on Fluid-Induced Vibration Power Harvesting of Square Columns under Different Attack Angles. (10th August 2017) - Zhang, Meng; Zhao, Guifeng; Wang, Junlei
Abstract : A model of the flow-vibration-electrical circuit multiphysical coupling system for solving square column vortex-induced vibration piezoelectric energy harvesting (VIVPEH) is proposed in this paper. The quasi steady state theory is adopted to describe the fluid solid coupling process of vortex-induced vibration based on the finite volume method coupled Gauss equation. The vibrational response and the quasi steady state form of the output voltage are solved by means of the matrix coefficient method and interactive computing. The results show that attack angles play an important role in the performance of square column VIVPEH, of which α = 45 ° is a relatively ideal attack angle of square column VIVPEH.